How Can We Evaluate Regeneration in Tourism? : Advancing Metrics and Methodologies for a Sustainable Transformation - Mohammad Shahidul Islam; Fariba Azizzadeh; Md Shamimul Islam (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
This study investigates the progression of regenerative tourism, highlighting the evolution from traditional sustainability models toward initiatives that proactively promote environmental restoration, social equity, and economic development. The discussion is rooted in Regenerative Development Theory and examines the critical need for developing comprehensive metrics and indicators. These tools are essential for assessing the impacts of regenerative tourism initiatives, allowing for a nuanced understanding of their contributions to environmental sustainability, social well-being, and economic prosperity. Through a conscientious methodology development and validation process, this work aims to provide stakeholders with the means to accurately evaluate and enhance the regenerative effects of tourism practices. The findings underscore the significance of regenerative tourism in guiding the industry towards a more sustainable and transformative future, offering valuable insights for policymaking, practical interventions, and the direction of future research.